Behavioral stress induces regionally-distinct shifts of brain mineralocorticoid and glucocorticoid receptor levels - Caudal, Dorian; Jay, Thérèse M.; Godsil, Bill P. (Frontiers in Behavioral Neuroscience, 2014)
Mineralocorticoid and glucocorticoid receptors (MRs and GRs) mediate the impact of stress on brain function primarily by affecting gene transcription in the cell nucleus. In vitro studies using hippocampal neurons indicate that MRs and GRs translocate to the nucleus after binding to the stress hormone corticosterone, yet the in vivo temporal dynamics of MR and GR levels in other limbic regions critical for the stress response, however, are largely unknown. Rats underwent an elevated platform stress procedure and brain tissue was sampled from the amygdala, medial prefrontal cortex, dorsal hippocampus and ventral hippocampus. By measuring MR and GR levels in the nuclear fraction from the tissue sampled, we observed striking shifts in the protein levels that varied by receptor, brain region and by the time after elevated platform stress. These findings indicate that the subcellular trafficking of corticosteroid receptors display distinct temporal dynamics in different limbic regions after behavioral stress. These heterogeneous effects could underlie contrasting regional responses to stress within the brain, and they highlight the importance for systems-level analysis of stress responsivity.